Amyloid fibrils containing fragmented ATTR may be the standard fibril composition in ATTR amyloidosis. (28th May 2013) - Ihse, Elisabet; Rapezzi, Claudio; Merlini, Giampaolo; Benson, Merrill D.; Ando, Yukio; Suhr, Ole B.; Ikeda, Shu-ichi; Lavatelli, Francesca; Obici, Laura; Quarta, Candida C.; Leone, Ornella; Jono, Hirofumi; et al.
Abstract: The clinical phenotype of familial ATTR amyloidosis depends to some extent on the particular mutation, but differences exist also within mutations. We have previously described that two types of amyloid fibril compositions exist among Swedish ATTRV30M amyloidosis patients, one consisting of a mixture of intact and fragmented ATTR (type A) and one consisting of mainly intact ATTR (type B). The fibril types are correlated to phenotypic differences. Patients with ATTR fragments have a late onset and develop cardiomyopathy, while patients without fragments have an early onset and less myocardial involvement. The present study aimed to determine whether this correlation between fibril type and phenotype is valid for familial ATTR amyloidosis in general. Cardiac or adipose tissues from 63 patients carrying 29 different TTR non-V30M mutations as well as 13 Japanese ATTRV30M patients were examined. Fibril type was determined by western blotting and compared to the patients' age of onset and degree of cardiomyopathy. All ATTR non-V30M patients had a fibril composition with ATTR fragments, except two ATTRY114C patients. No clear conclusions could be drawn about a phenotype to fibril type correlation among ATTR non-V30M patients. In contrast, Japanese ATTRV30M patients showed a similar correlation as previously described for Swedish ATTRV30M patients. This study shows that a fibril composition with fragmented ATTR is very common in ATTR amyloidosis, and suggests that fibrils composed of only full-length ATTR is an exception found only in a subset of patients.